PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. TRI ASRI DESINDOTAMA \TANGERANG SELATAN - Purnama Dinata; Eko Sudarso (Journal of Research and Publication Innovation, 2025)
The research in this thesis is motivated by the phenomenon of the increasing number of companies in the construction sector. The competition has become stronger and more intense, requiring companies to have a strong strategy. One such strategy is improving the work environment infrastructure, which supports employee productivity, along with appropriate training. As a result, employee productivity will increase, leading to output that meets company targets. This study aims to examine the influence of Training and Work Environment on Employee Performance at PT. Tri Asri Desindotama Tangerang Selatan, both separately and simultaneously. The method used is Saturated Sampling with a population of 75, where all members of the population are made respondents. Data were collected through observation and questionnaires, and analyzed using validity tests, reliability tests, classical assumptions, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The results show that Training has a significant effect on Employee Performance (t count > t table) with the regression equation Y = 7.895 + 0.839X1, and a correlation value of 0.854, indicating a strong relationship. The Work Environment also has a significant effect on Employee Performance (t count > t table) with the regression equation Y = 8.473 + 0.829X2 and a correlation value of 0.820, indicating a strong relationship. Simultaneously, both variables influence Employee Performance (F count > F table) with the regression equation Y = 4.826 + 0.543X1 + 0.370X2 and a correlation value of 0.879, showing a strong relationship, while the coefficient of determination is 77.2%, indicating that 22.8% is influenced by other factors. This means that if there is an improvement in the training and work environment variables, employee performance will also improve. The variable that has the most dominant influence on employee productivity is the training variable, at 72.9%.